Sex-Based Predictors of Male and Female Property Crime Arrest Rates: Disadvantage and Drug Use. Issue 2 (4th March 2019) - Roth, Jeffrey J.; King, Laura L.
Abstract : A large body of research has considered the relationship between crime and structural indicators. However, despite trends in the gender gap in offending, fewer studies have separately examined the effects of structural variables on both male and female offending. The present study examined that question through a macro-level examination of property crime across large U.S. cities using data from the Uniform Crime Report and the American Community Survey. The predictors included theoretically supported indicators of disadvantage and drug accessibility/use that were disaggregated by sex. Although the findings indicated some similarities in predictors of male and female arrest rates, they highlighted some important differences as well.